Transposable element Pot2 based diversity analysis of Magnaporthe oryzae isolates from rice blast endemic regions of South India - Deshmukh, Dnyaneshwar B; Prashanthi, S K (Indian Journal of Plant Protection, 2020)
Thirty-four isolates of the rice blast pathogen, Magnaporthe oryzae, collected from various disease endemic regions of South India were used for cultural and molecular diversity study. The cultural characteristics of M. oryzae isolates viz., growth type, colour of the vegetative growth, number of days needed to form conidia, length and width of conidia showed variation within and across the locations. Transposable element, Pot2 specific to M. oryzae was the basis of molecular diversity in which variation present in the two intervening sequences of repetitive elements Pot2 was considered. Pot2 element based PCR was used to generate fingerprint profile of 34 M. oryzae isolates. Size of Pot2 element in the isolates varied from 400 bp to 8 kb. Phylogenetic cluster analysis using Pot2 fingerprint grouped out 34 isolates into four different clusters, cluster-1, 2, 3 and 4 which shared low similarity value of 0.3. The differences in the studied isolates varied from 25% to 96%. The high level of genetic diversity at Gangavathi (89%), Mugad (60%) and Mandya (96%) was noticed between leaf and neck blast pathogen populations. The diversity was evident among the isolates collected within location as well as across the locations. The study revealed the morphological and molecular diversity of M. oryzae collected at different phenological stages of rice in south India.